2017
DOI: 10.1371/journal.pone.0180412
|View full text |Cite
|
Sign up to set email alerts
|

Simulated space radiation-induced mutants in the mouse kidney display widespread genomic change

Abstract: Exposure to a small number of high-energy heavy charged particles (HZE ions), as found in the deep space environment, could significantly affect astronaut health following prolonged periods of space travel if these ions induce mutations and related cancers. In this study, we used an in vivo mutagenesis assay to define the mutagenic effects of accelerated 56Fe ions (1 GeV/amu, 151 keV/μm) in the mouse kidney epithelium exposed to doses ranging from 0.25 to 2.0 Gy. These doses represent fluences ranging from 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…The mutagenic potential of charged-particle radiation has been extensively studied in cell cultures and in vivo , though relatively little attention has been devoted to studying mutagenic effects on brain tissues ( Gauny et al, 2001 ; Wiese et al, 2001 ; Yatagai, 2004 ; Bielefeldt-Ohmann et al, 2012 ; Sridharan et al, 2015 ). Previous in vivo work demonstrated that low doses of 56 Fe particles are capable of eliciting genome-wide SNPs, which played an important role in the loss of heterozygosity in explanted kidney epithelial cells ( Turker et al, 2017 ). Protons have likewise been observed to induce loss of heterozygosity in explanted kidney epithelial cells at higher dosages (1–5 Gy), but not at a more mission-relevant dose (0.5 Gy) ( Kronenberg et al, 2009 ; Turker et al, 2013 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutagenic potential of charged-particle radiation has been extensively studied in cell cultures and in vivo , though relatively little attention has been devoted to studying mutagenic effects on brain tissues ( Gauny et al, 2001 ; Wiese et al, 2001 ; Yatagai, 2004 ; Bielefeldt-Ohmann et al, 2012 ; Sridharan et al, 2015 ). Previous in vivo work demonstrated that low doses of 56 Fe particles are capable of eliciting genome-wide SNPs, which played an important role in the loss of heterozygosity in explanted kidney epithelial cells ( Turker et al, 2017 ). Protons have likewise been observed to induce loss of heterozygosity in explanted kidney epithelial cells at higher dosages (1–5 Gy), but not at a more mission-relevant dose (0.5 Gy) ( Kronenberg et al, 2009 ; Turker et al, 2013 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo work demonstrated that low doses of 56 Fe particles are capable of eliciting genome-wide SNPs, which played an important role in the loss of heterozygosity in explanted kidney epithelial cells ( Turker et al, 2017 ). Protons have likewise been observed to induce loss of heterozygosity in explanted kidney epithelial cells at higher dosages (1–5 Gy), but not at a more mission-relevant dose (0.5 Gy) ( Kronenberg et al, 2009 ; Turker et al, 2013 , 2017 ). Whereas the role of charged-particle radiation on epigenetic remodeling of the hippocampus has recently placed attention on the genetic influence of radiation-dependent behavioral changes, no SNP analysis has yet been conducted on hippocampal tissues ( Impey et al, 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, using mouse kidney cell lines, it has been reported that the interstitial LOH pattern is induced as a delayed effect of gamma, proton and iron-ion radiation exposure. 45 In those studies, however, it was not clear whether the LOH was caused by chromosomal missegregation, mitotic recombination or deletion. Therefore, in the present study we examined the copy number of the Tsc2 locus by array CGH analysis and found that LOH of the interstitial deletion type was observed only in tumors of irradiated groups ( Figure 2B).…”
Section: Discussionmentioning
confidence: 97%
“… A high frequency of the interstitial LOH pattern at the tumor‐suppressor Ikaros locus has also been reported in radiation‐induced thymic lymphomas in mice, compared with spontaneously developed or alkylating agent‐induced lymphomas . Furthermore, using mouse kidney cell lines, it has been reported that the interstitial LOH pattern is induced as a delayed effect of gamma, proton and iron‐ion radiation exposure . In those studies, however, it was not clear whether the LOH was caused by chromosomal missegregation, mitotic recombination or deletion.…”
Section: Discussionmentioning
confidence: 99%
“…其作用方式有两种: 一是通过带电粒子与 DNA分子的相互作用引起DNA双链断裂 [9,10] , 导致基 因组不稳定性 [11] ; 二是通过生成自由基对DNA造成间 接损伤 [12] . 空间辐射还会导致染色体变异率增加 [13] , 引起微核的形成与变异 [14,15] , 造成染色体组重排, 这可 能是辐射致癌的起始步骤 [16] . 此外, 空间辐射还会影响 细胞凋亡和周期的调节 [12,17] .…”
unclassified